The impact of perioperative red blood cell transfusion on the prognosis of colorectal cancer - Jiang, Ting; Liu, Kun; Chen, Zexin (Frontiers in Surgery, 2022)
Background: There is no consensus on the effect of red blood cell transfusion on colorectal cancer (CRC). This study examined the impact of perioperative red blood cell transfusion on postoperative complications, recurrence, and mortality in patients with CRC. Methods: In this retrospective cohort study, 219 CRC patients admitted to Chongqing Emergency Medical Center, and Chongqing University Central Hospital from 2008 to 2019 were divided into transfusion (n=75) and non-transfusion (n=144) groups. Univariate and multivariate Logistic regression analysis were used to analyze the effects of blood transfusion on the severity of postoperative complications in patients with CRC, and univariate and multivariate Cox regression was performed to analyze the effects of blood transfusion on postoperative death and recurrence. Results: Twenty-two (29.33%) patients in the transfusion group were intermediate or advanced severity of postoperative complications, 31 (41.33%) patients died in the transfusion group, and 55 (73.33%) patients occurred recurrence of the CRC, with the median follow-up time being 24.57(14.50,36.37) months. Our result showed that perioperative red blood cell transfusion was associated with an increased risk of intermediate or advanced severity of postoperative complications in CRC patients [odds ratio (OR)=3.368, 95%CI: 1.146-9.901]. And perioperative red blood cell transfusion increased the risk of postoperative death [hazard ratio (HR)=2.747, 95%CI: 1.048-7.205] and recurrence in patients with CRC (HR=2.168, 95%CI: 1.192-3.943). Conclusion: Our finding demonstrated that perioperative red blood cell transfusion was associated with severity of complications, recurrence, and death in CRC patients. However, further studies are still needed to confirm the adverse effects of red blood cell transfusions in CRC patients.